2013
DOI: 10.1209/0295-5075/103/38002
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic compressibility of dense granular shear flows

Abstract: It has been conjectured by Bagnold [1] that an assembly of hard non-deformable spheres could behave as a compressible medium when slowly sheared, as the average density of such a system effectively depends on the confining pressure. Here we use discrete element simulations to show the existence of transverse and sagittal waves associated to this dynamical compressibility. For this purpose, we study the resonance of these waves in a linear Couette cell and compare the results with those predicted from a contin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 44 publications
1
41
0
Order By: Relevance
“…In particular, Trulsson et al (2013) showed that acoustic waves could be transmitted through shear flows when compressibility was taken into account and Pouliquen & Forterre (2009) and Kamrin & Henann (2015) were able to model the point of transition between static and moving material on a frictional inclined plane. However, these effects introduce additional complexity into the governing equations and require new numerical schemes to be developed in order to solve them.…”
Section: N T Graymentioning
confidence: 99%
“…In particular, Trulsson et al (2013) showed that acoustic waves could be transmitted through shear flows when compressibility was taken into account and Pouliquen & Forterre (2009) and Kamrin & Henann (2015) were able to model the point of transition between static and moving material on a frictional inclined plane. However, these effects introduce additional complexity into the governing equations and require new numerical schemes to be developed in order to solve them.…”
Section: N T Graymentioning
confidence: 99%
“…More generally, this approach has been successfully applied in different geometries [2,3], e.g. silo discharge [11], granular chute flows [12][13][14][15] and granular column collapse [16,17], as well as to describe dynamic compressibility effects associated with spontaneous oscillatory motion [18,19]. Interestingly, experiments and numerical simulations have recently provided evidence for limie-mail: somfai.ellak@wigner.mta.hu tations of the μ(I)-rheology, when some non-local effects come into play (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Forterre & Pouliquen (2002) showed that kinetic theory taken in the compressible limit could reproduce the instability leading to the longitudinal vortices observed in their experiments. Dense granular flows in the inertial regime might also be strongly affected by acoustic waves, resonances and instabilities due to dynamic density fluctuations as recently observed in numerical and experimental studies (Melosh 1979;Börzsönyi et al 2009;Brodu et al 2013;Trulsson et al 2013;Krishnaraj & Nott 2016). A classic example of such instability is also found in the pulsating flows frequently observed out of silos (Muite et al 2004).…”
Section: Introductionmentioning
confidence: 72%
“…At this point, it is interesting to estimate the importance of the dynamical pressure developing while shearing a granular media and its possible coupling with the main flow (Trulsson et al 2013). Based on the experimental scaling (3.2) and the definition of the inertial number (3.1), we may express the friction coefficient µ and the pressure at equilibrium p eq as a function of the volume fraction φ:…”
Section: A Compressible µ(I) Rheologymentioning
confidence: 99%